An analysis of changes in resistivity of general reservoir dams based on 4D inversion of time-lapse resistivity data. Issue 1 (1st December 2016) - Song, Seo Young; Kim, Bitnarae; Nam, Myung Jin; Lim, Sung Keun
Abstract : There are many reservoir dams in the South Korea for the purpose of agriculture. It is necessary to monitor these agricultural facilities to prevent accidents such as water leakage in the deteriorating equipment in advance. Resistivity surveys are commonly applied to determining leakage of water under the dams. Resistivity monitoring had been conducted every six hours during September, 2015 at the Cheongcheon reservoir on the Chungcheongnam-do in the south-west of the South Korea. Prior to analysing this monitoring data, it is needed to pick specific section of the data having meaningful changes of resistivity structure. Forward modelling was performed to determine variations of resistivity based on the variations of characteristics under the dams, consequently selecting proper dataset and doing inversion well. To reflect various underground feature like distorted dam structure and determine exactly, I developed three-dimensional (3D) electrical-resistivity modelling algorithm, using finite element method (FEM) based on tetrahedron element. Also, I examined rate of resistivity variation on the crest of the dam according to the changes of properties of reservoir. On the basis of this rate, valuable monitoring data were chosen and used to do time-lapse resistivity inversion. We also improved three-dimensional inversion algorithm to 4D algorithm, adding time constraint section, considering the rate of changes as time passes by. From this method, we could evaluate conditions of reservoir dam and avoid damage of human life or property by dam collapse.